Анализ и развитие пузырьковой модели стадии формирования высоковольтного пробоя водного промежутка - Жекул, Василий Григорьевич; Хвощан, Олег Вильямович; Смирнов, Алексей Петрович; Тафтай, Эдуард Иванович; Швец, Иван Сафронович (НТУ "ХПИ", 2018)
Выполнен обзор и анализ современных представлений о предпробойных процессах при высоковольтном электрическом разряде в жидкости. Показано, что "пузырьковая" ("bubble") модель зажигания разряда применима при напряженности электрического поля (36 – 180) кВ/см. По результатам экспериментальных исследований электрических характеристик разряда в водном электролите при повышенном гидростатическом давлении и минимальном напряжении, обеспечивающем зажигание разряда, получила дальнейшее развитие пузырьковая модель стадии формирования его высоковольтного пробоя. Предложено качественное описание трех фаз стадии формирования плазменного канала в жидком электролите.

A high-voltage underwater electric explosion, realized by discharging a capacitor into a water gap, is characterized by three main stages: the stage of formation of the plasma channel, the channel stage and post-discharge one. Substantially, the channel, post-discharge stages and the efficiency of energy release in the channel and the increase in the hydrodynamic effect on the object being processed depend on the parameters of the stage of formation. The purpose of the work was to review the existing mechanisms for the formation of a high-voltage discharge channel with the analysis and development of a bubble model of the stage of formation of water gap breakdown. We have applied the analysis of existing theories on the formation of a high-voltage discharge channel, the carrying out of electrophysical studies with the processing of the obtained data. A review and analysis of modern concepts of pre-breakdown processes in a high-voltage electric discharge in a liquid showed that the "bubble" model of the ignition of a discharge is applicable at an electric field strength (36 – 180) kV/cm. We have further developed the bubble model of the stage of formation of high-voltage break-down on the results of experimental studies of the electrical characteristics of the discharge in the aqueous electrolyte with increased hydrostatic pressureand minimum voltage providing ignition of the discharge. A qualitative description of three phases of the stage of formation of the plasma channel in the liquid electrolyte is proposed. We have further developed the bubble model of the stage of formation of high-voltage breakdown of the liquid electrolyte on the results of experimental studies of the electrical characteristics of the discharge in the aqueous electrolyte with increased hydro-static pressure and minimum voltage providing ignition of the discharge. A qualitative variation of the resistance of the gap in the pre-breakdown stage of the discharge is considered. Determination of the scientific basis for creating a methodology for calculating the pre-breakdown characteristics of an electric discharge to improve the efficiency of electric discharge devices.
Analysis and development of the bubble model of the formation stage of high-voltage breakdown of the water gap
Keywords: высоковольтный электрический разряд; жидкий электролит; осциллограмма; предпробойные процессы; high-voltage electric discharge; liquid electrolyte; pre-breakdown processes